Textbook of Pulmonary Vascular Disease - Yuan, Jason X. -J.; Garcia, Joe G.N.; West, John B.; Hales, Charles A.; Rich, Stuart; Archer, Stephen L.; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
The Textbook of Pulmonary Vascular Disease combines basic scientific knowledge on the pulmonary circulatory system at levels of the molecule, cell, tissue, and organ with clinical diagnosis and treatment of pulmonary vascular diseases. State-of-the-art techniques and their potential applications in research, diagnosis, and treatment of pulmonary vascular diseases are also covered. Jason X.-J. Yuan, MD, PhD is Professor of Medicine, University of Illinois at Chicago, Chicago, IL Joe G.N. Garcia, MD is Earl Banes Professor of Medicine and Vice Chancellor for Research, University of Illinois at Chicago, Chicago, IL Charles A. Hales, MD is Professor of Medicine, Massachusetts General Hospital, Harvard Medical School, Boston, MA Stuart Rich, MD is Professor of Medicine, University of Chicago, Chicago, IL Stephen L. Archer, MD is Harold Hines Jr. Professor of Medicine and Chief of Cardiology, University of Chicago, Chicago, IL John B. West, MD, PhD, DSc is Distinguished Professor of Physiology and Medicine, University of California, San Diego, La Jolla, CA
The Human Pulmonary Circulation: Historical Introduction -- Microcirculation of the Lung: Functional and Anatomic Aspects -- Pulmonary Vascular Development -- Pulmonary Vascular Function -- Pulmonary Vascular Mechanics -- Modeling of the Pulmonary Vasculature -- Metabolic and Clearance Function at the Pulmonary Microvascular Endothelial Surface in Pulmonary Hypertension -- The Pharmacology of the Major Vasoactive Mediators Relevant to the Pathogenesis of Pulmonary Hypertension -- The Normal Fetal and Neonatal Pulmonary Circulation -- Excitation-contraction Coupling and Regulation of Pulmonary Vascular Contractility -- Endothelial Regulation of Pulmonary Vascular Tone -- Acute Lung Injury: The Injured Lung Endothelium, Therapeutic Strategies for Barrier Protection and Vascular Biomarkers -- Ion Channels and Transporters in the Pulmonary Vasculature: A Focus on Smooth Muscle -- Receptor-mediated Signal Transduction and Cell Signaling -- Role of Calcium as a Second Messenger in Signaling: A Focus on Endothelium -- Caveolae and Signaling in Pulmonary Vascular Endothelial and Smooth Muscle Cells -- The Chemistry of Biological Gases -- Role of Oxygen-derived Species in the Regulation of Pulmonary Vascular Tone -- Mitochondrial ROS and Redox State in Pulmonary Vascular O2 Sensing -- Cellular and Molecular Mechanisms of Pulmonary Vascular Smooth Muscle Cell Proliferation -- Role of Ca2+ in Vascular Smooth Muscle Gene Expression and Proliferation -- Biochemistry and Cellular Mechanisms of Apoptosis in Vascular Smooth Muscle and Endothelial Cells -- The Coagulation Cascade and its Regulation -- Platelets in Pulmonary Vascular Physiology and Pathology -- Lysis and Organization of Pulmonary Thromboemboli -- Interactions of Leukocytes and Coagulation Factors with the Vessel Wall -- Interaction of the Plasminogen System with the Vessel Wall -- Endothelial Apoptosis and Repair in Pulmonary Arterial Hypertension -- Bronchial Arterial Circulation in the Human -- Animal Models of Pulmonary Hypertension -- Transgenic and Gene Targeted Mouse Models for Pulmonary Hypertension -- Animal Models of Increased Lung Vascular Permeability -- Isolation and Culture of Pulmonary Vascular Smooth Muscle and Endothelial Cells -- Conventional Patch Clamp Techniques and High-throughput Patch Clamp Recordings on a Chip for Measuring Ion Channel Activity -- Measurement of Pulmonary Vascular Structure and Pulmonary Blood Distribution by MDCT and MR Imaging Techniques -- Quantification of DNA, RNA and Protein Expression -- Gene Cloning, Transfection and Mutagenesis -- Approaches for Manipulation of Gene Expression -- Bioinformatics, Genomics, and Functional Genomics: Overview -- Genomic Application to Study Pulmonary Hypertension -- Proteomics and Functional Proteomics -- Maintenance, Propagation and Differentiation of Human Embryonic Stem Cells and Induced Pluripotent Stem Cells -- Identification of Adult Stem and Progenitor Cells in the Pulmonary Vasculature -- Differentiation of Embryonic Stem Cells to Vascular Cell Lineages -- Statistics and Clinical Data Analysis: A Reference Guide -- Hypoxic Pulmonary Vasoconstriction -- Pathogenic Roles of Ca2+ and Ion Channels in Hypoxia-mediated Pulmonary Hypertension -- Roles of Endothelium-derived Vasoactive and Mitogenic Factors in the Development of Chronic Hypoxia-mediated Pulmonary Hypertension -- Oxygen-sensitive Transcription Factors and Hypoxia-mediated Pulmonary Hypertension -- Developmental Regulation of Pulmonary Vascular Oxygen Sensing -- Pulmonary Vascular Remodeling by High Oxygen -- Pulmonary Vascular Remodeling: Cellular and Molecular Mechanisms -- Carbon Monoxide and Heme Oxygenase in the Regulation of Pulmonary Vascular Function and Structure -- Shear Stress, Cell Signaling and Pulmonary Vascular Remodeling -- Pulmonary Hypertension and the Extracellular Matrix -- Role of Progenitor Cells in Pulmonary Vascular Remodeling -- Receptor Signaling in Pulmonary Arterial Hypertension -- Role of Endothelium in the Development of Pulmonary Hypertension -- Coagulation and the Vessel Wall in Pulmonary Embolism -- Alveolar Epithelial Fluid Transport in Lung Injury -- High Altitude Pulmonary Edema -- Statins and Acute Lung Injury -- Genomics of Acute Lung Injury and Vascular Barrier Dysfunction -- Ventilator-induced Mechanical Stress and Lung Vascular Dysfunction -- Classification of Pulmonary Hypertension: History and Perspectives -- Epidemiology of Pulmonary Arterial Hypertension -- Air Pollution and the Pulmonary Vasculature -- Idiopathic Pulmonary Arterial Hypertension -- Genetics of Familial and Idiopathic Pulmonary Arterial Hypertension -- Pulmonary Arterial Hypertension Related to Scleroderma and Collagen Vascular Diseases -- Pathology and Management of Portopulmonary Hypertension -- Pathobiology and Treatment of Pulmonary Hypertension in HIV Disease -- Pulmonary Arterial Hypertension Secondary to Anorexigens and Other Drugs and Toxins -- Pulmonary Arterial Hypertension Related to Gauchers, Sarcoidosis and Other Disorders -- Pediatric Pulmonary Hypertension: An Integrated View from Pediatric Subspecialists -- Persistent Pulmonary Hypertension of the Newborn: Mechanisms and Treatment -- The Pulmonary Circulation in Congenital Heart Disease -- Pulmonary Hypertension Secondary to Congenital Systemic to Pulmonary (Left-to-Right) Shunts -- Surgical Evaluation of Congenital Heart Disease-associated Pulmonary Hypertension -- Pulmonary Veno-occlusive Disease -- Left Ventricular Diastolic Heart Function and Pulmonary Hypertension -- Pulmonary Hypertension Associated with Chronic Obstructive Pulmonary Diseases -- Pulmonary Hypertension Associated with Interstitial Lung Disease -- High Altitude Pulmonary Hypertension -- Pulmonary Hypertension and Congenital Heart Defects at High Altitude -- Pulmonary Embolism and Deep Vein Thrombosis -- Pulmonary Hypertension Due to Pulmonary Embolism and Thromboembolic Obstruction of Proximal and Distal Pulmonary Arteries -- Risk Factors for Chronic Thromboembolic Pulmonary Hypertension -- Evaluation of Small Vessel Arteriopathy in Chronic Thromboembolic Pulmonary Hypertension -- Hemolytic Anemia Associated Pulmonary Hypertension: Sickle Cell Disease and Thalassemia-associated Pulmonary Hypertension -- Pulmonary Hypertension due to Schistosomiasis -- Pulmonary Hypertension due to Capillary Hemangiomatosis -- Molecular Basis of Right Ventricular Hypertrophy and Failure in Pulmonary Vascular Disease -- Right Ventricular Dysfunction in Pulmonary Hypertension -- Large Vessel Pulmonary Arteritis -- Tumors of the Pulmonary Vascular Bed -- Cor Pulmonale -- Pregnancy and Contraception in Patients with Pulmonary Arterial Hypertension -- Cardiac Catheterization in the Patient with Pulmonary Hypertension -- Imaging of Pulmonary Vascular Diseases -- Histological and Pathological Diagnosis of Pulmonary Hypertension: Pathological Classification of Pulmonary Vascular Lesions -- Echocardiography in Pulmonary Vascular Disease -- Calcium Channel Blockers in the Treatment of Pulmonary Arterial Hypertension -- Prostacyclin and Prostaglandins -- Endothelin Receptor Antagonists for the Treatment of Pulmonary Arterial Hypertension -- Phosphodiesterase Inhibitors in the Treatment of Pulmonary Hypertension -- Nitric Oxide for Children -- The Serotonin System as a Therapeutic Target in Pulmonary Hypertension -- Combination Therapy for Pulmonary Arterial Hypertension -- Thrombolytic and Anti-coagulant Therapy for Pulmonary Embolism and Chronic Thromboembolic Pulmonary Hypertension -- Nursing Care of Patients with Pulmonary Arterial Hypertension -- Atrial Septostomy -- Evaluation of Patients with Chronic Pulmonary Thromboembolic Pulmonary Hypertension for Pulmonary Endarterectomy -- Pulmonary Endarterectomy -- Evaluation of Patients with Pulmonary Hypertension for Lung Transplantation -- Lung Transplantation for Pulmonary Hypertension -- Living-donor Lower Lobar Lung Transplantation for Pulmonary Arterial Hypertension -- Results of Lung Transplantation -- Index.
Keywords: Medicine; Critical care medicine; Cardiology; Medicine & Public Health; Cardiology; Intensive / Critical Care Medicine